Determinan Kesejahteraan Anak Usia Dini dalam Keluarga dengan Kepala Rumah Tangga Perempuan di Indonesia - Setyanti, Axellina M; Syafitri, Wildan (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
This study analyzes the determinants of early childhood well-being in female-headed households in Indonesia using data from the 2022 National Socioeconomic Survey (SUSENAS), covering 85,074 households with children aged 0–5 years. Using binary logistic regression, the analysis focuses on four key indicators: complete immunization, food adequacy, access to improved sanitation, and access to safe drinking water. The results show that children in female-headed households are significantly less likely to receive adequate and diverse food as well as complete immunization, compared to those in male-headed households. However, these households are more likely to provide access to improved sanitation and safe drinking water. Other influential factors include the household head’s education, home ownership, internet access, and residential location. The findings highlight that the gender of the household head plays a crucial role in shaping child well-being. Accordingly, gender-responsive policies are essential to address the structural vulnerabilities of female-headed households, by enhancing economic capacity, improving access to gender-sensitive services, and implementing targeted, data-driven interventions. Additionally, families, especially those led by women, are encouraged to strengthen their literacy in child health and nutrition and to utilize public services that support the fulfillment of children's basic rights.